2007
DOI: 10.1177/0363546506291404
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lateral Meniscal Allograft Sizing on Contact Mechanics of the Lateral Tibial Plateau

Abstract: Preoperative radiographic sizing needs to be performed precisely to identify a suitable lateral meniscal allograft. A mismatch may be the reason for failure of the allograft or subsequent development of degenerative changes. A mismatch on graft selection of less than 10% of the size of the original meniscus may be acceptable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
141
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(155 citation statements)
references
References 22 publications
10
141
1
Order By: Relevance
“…Indeed, degenerative changes associated with meniscectomies have been linked to increased joint contact stress (hereafter referred to as contact pressure) in the adjacent articular cartilage as measured in vitro [18][19][20][21][22][23][24][25][26][27] . To date, however, experimental models have been primarily conducted under static or quasi-static uniaxial loading conditions 8,[28][29][30][31][32][33] . Given the sensitivity of joint contact pressures to the magnitude and direction of an applied load 34,35 , these models do not accurately capture the physiological effect of meniscal repair or meniscectomy on knee contact mechanics.…”
mentioning
confidence: 99%
“…Indeed, degenerative changes associated with meniscectomies have been linked to increased joint contact stress (hereafter referred to as contact pressure) in the adjacent articular cartilage as measured in vitro [18][19][20][21][22][23][24][25][26][27] . To date, however, experimental models have been primarily conducted under static or quasi-static uniaxial loading conditions 8,[28][29][30][31][32][33] . Given the sensitivity of joint contact pressures to the magnitude and direction of an applied load 34,35 , these models do not accurately capture the physiological effect of meniscal repair or meniscectomy on knee contact mechanics.…”
mentioning
confidence: 99%
“…Despite plain radiograph are more commonly used for graft sizing [6], some studies have demonstrated that the use of MRI is more accurate than plain radiographs [56,57]. An oversized and undersized graft increases forces across the articular cartilage and allograft, respectively [59]. Dienst et al suggested that a mismatch up to 10% of the size of the original meniscus would be acceptable [59].…”
Section: Graft Sizingmentioning
confidence: 99%
“…An oversized and undersized graft increases forces across the articular cartilage and allograft, respectively [59]. Dienst et al suggested that a mismatch up to 10% of the size of the original meniscus would be acceptable [59]. The improvement of graft sizing and the better understanding of tolerance and consequences of size mismatch warrant further research.…”
Section: Graft Sizingmentioning
confidence: 99%
“…27 We evaluated the fraction of data points that met this criterion for each sheep. The fraction of points that fell within AE10% error was greater than 33% for all sheep across all fabrication methods (Table 2).…”
Section: Success Criteriamentioning
confidence: 99%
“…22 Here we focus on the generation of anatomically accurate engineered menisci. The meniscus is pertinent for three reasons: (1) clinical relevance-meniscal lesions are one of the most common injuries in the knee 23 with >1.5 million knee surgeries involving the meniscus and usually resulting in the removal of damaged tissue as opposed to repair or replacement 23 ; (2) complex geometrypredicting and calculating meniscal shape based on magnetic resonance imaging (MRI) images can be quite time consuming, and the algorithms for making these predictions are continually being modified [24][25][26][27][28] ; (3) accurate meniscal geometry is crucial for proper mechanical function of the knee joint, 29 its primary function being to aid in joint load distribution, thus decreasing contact stresses on the underlying articular cartilage. A deviation by >10% in size matching 27 can result in detrimental joint loading and more rapid development of osteoarthritis.…”
Section: Introductionmentioning
confidence: 99%